Periodontal surgical treatment for gingival smile correction: integrative literature review (Research, Society and Development, 2022)
When there is excessive exposure of the gingiva, the gummy smile arises, a non-pathological condition that leads to an aesthetic disharmony. The display of up to 2-3 mm or less of gingival tissue is seen as harmonic, on the other hand, more than 4 mm is considered gingival. Understanding the multifactorial etiology of gummy smile is essential for a good diagnosis of the main factors related to each case, a factor that also reflects in the elaboration of a correct and effective treatment plan. The present integrative literature review aims to describe the surgical approaches for the treatment of gummy smile. For the elaboration of the study, the Pubmed database was used, in which the PICO strategy was used. After the inclusion and exclusion criteria, 13 articles were selected. The results showed two periodontal surgical therapies: flap with internal bevel associated with osteotomy and lip repositioning. Clinical crown augmentation flaps seem to have greater predictability across studies. Lip repositioning surgery showed divergence between the authors about the effectiveness of the techniques presented, and more studies are needed to elucidate this issue. Although it is noted that most authors concluded that the approaches were satisfactory, further studies with a larger number of samples, systematic reviews and meta-analyses are needed to assess the long-term predictability of the treatments presented.